Quality Practice Teaching Experience in Cooperating Schools: Building Foundations for Effective Teacher Education - Santiago, Lilia M. (Future Science / FSH-PH Publications, 2024)
A study was conducted in the Tarlac City Schools Division, Philippines, to evaluate the practice teaching experiences of student interns in line with Republic Act No. 7722, known as the